The Role of Social Capital in Entrepreneurial Success in the Digital Economy - Mendong, Muh. Mu'min (Professorline, 2025)
This study explores the role of social capital in entrepreneurial success in the context of Indonesia’s digital economy. Social capital, encompassing social networks, trust, and norms of reciprocity, has become a critical factor in the rapidly growing digital entrepreneurship ecosystem. Using a mixed methods approach that combines a survey of 150 digital entrepreneurs and in-depth interviews with 15 entrepreneurs, this study investigates how three dimensions of structural, relational, and cognitive social capital contribute to different aspects of entrepreneurial success. The results of the Structural Equation Modeling (SEM) analysis show that the structural dimension of social capital has a strong influence on business growth and innovation, the relational dimension has a significant impact on financial performance and sustainability, while the cognitive dimension contributes to business innovation and sustainability. Qualitative analysis reveals the importance of “authentic digital social capital” that emphasizes the quality of interactions and engagement over the quantity of connections. This study also finds a moderating effect of the type of digital venture and the stage of venture development, underscoring the importance of a contextual approach in social capital development strategies. The theoretical and practical implications of these findings are discussed in the context of developing a sustainable digital entrepreneurship ecosystem.